VERBAL AND NON-VERBAL COMMUNICATION: TEACHER TALK IN ENGLISH CLASSES IN JAMBI - Muhammad Guntar (International Journal of Business English and Communication, 2023)
The purposes of this research were to analyse what forms of verbal and non-verbal communication and the implementation of Teacher Talk applied in EFL classrooms. The research utilized descriptive qualitative method. The participants of the research were two English teachers in senior high school level in Jambi Province. The data were collected in the form of video recording and then data was analysed according to FLINT System and Darn Classification. The result showed that all elements of verbal communication in FLINT system were used in these EFL classrooms. Meanwhile, most of elements in nonverbal communication according to Darn Classification happened in these classes, they are Kinesics, Proxemics, Oculesics, Vocalics, Sound of symbol, Silence, Adornment, Posture, Locomotion, and Expression. Furthermore, the teachers applied teacher talk by using verbal and nonverbal communication to help students understand and make them engaged in English classes.